Proses Adaptasi Komunitas Wisata untuk Mencapai Ketahanan di Kampung Wisata Rejowinangun Yogyakarta Selama Pandemi Covid-19 - Asyila, Safira (Gadjah Mada Journal of Tourism Studies, 2023)
The social and economic aspects of Rejowinangun Tourism Village, which comprises five tourism clusters, were significantly impacted by the COVID-19 pandemic. This study seeks to comprehend how the tourism community in Rejowinangun Tourism Village reacted to the crisis caused by the COVID-19 pandemic and the issues mentioned above. Conducting this research is crucial to identifying the determinants of tourism resilience in tourist villages amidst the COVID-19 pandemic. This study employs a qualitative descriptive methodology. The data collection procedure comprised a literature review, semi-structured interviews, and field observations. The tourism industry reacted to the COVID-19 pandemic by implementing human resource capacity-building initiatives, demonstrating adherence to health protocols, and implementing digitization innovations. In addition to the tourism village community comprising the community and the tourism cluster, the government plays a significant role in shaping the tourism community's resilience in the face of the COVID-19 pandemic.